Improving the Quality of Private Islamic Religious Universities in Jambi Province Through Leadership Management - Hasanah, Neneng; Syukri, Ahmad; Jailani, M. Syahran (Journal of Social Work and Science Education, 2023)
The goal of this study is to examine leadership management in increasing the quality of PTKIS in Jambi Province. This study employs a qualitative technique with a descriptive-analytical focus. Data was collected through observation, interviews, and documentation. Purposive sampling was used to identify research subjects. Techniques for data analysis include data reduction, data display, conclusion, and verification. Reliability through prolonged participation procedures, observational accuracy, data triangulation, and promoter consultation. The findings of this study are the leadership planning in improving the quality of PTKIS in Jambi Province by compiling a work program, distributing existing human resources in a number of predetermined tasks, even though many human resources are not in accordance with their expertise, carrying out existing work programs, seeking accreditation that is consistent with standards, recruiting lecturers based on their competence, and ensuring the continuity of the lecturers.